Microstructural changes of carbonaceous monoliths synthesized via hydrothermal method - Lim, Hong Ngee; Kassim, Anuar; Lim, Su Pei; Nizar, N. S. Rastam; Huang, Nay Ming (Sociedad Chilena de Quimica, 2011)
Carbonaceous monoliths were successfully synthesized via a facile hydrothermal processing route using phenol as a carbon precursor. The x-ray diffraction (XRD) patterns revealed distinguishable (002) and (100) planes of graphite at approximately 2θ = 23° and 44°, respectively. The fourier transform infrared (FTIR) spectroscopy corresponded to the chemical bonds of graphite, which were C=C and C-H. The carbonaceous monoliths exhibited interesting morphological changes as a result of varying the type of polymer which acted as a structure directing agent, mass of polymer, mass of phenol and hydrothermal temperature before and after calcination.